The Effect of Cabbage Leaf Compress (Brassica Oleracea Var.Capitata) on Breast Swelling in Postpartum Mothers at the Nining Primary Clinic Lubuk Pakam - Fiyola Ladyvia; Natasha Elga Haryono; ismah khaerunisa (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2026)
Breast engorgement is a common problem in postpartum mothers, caused by milk stasis due to constriction of the lactiferous ducts or inadequate emptying of the mammary glands. In Indonesia, this condition affects approximately 10–20% of breastfeeding mothers, or around 2.3 million women. The 2024 Indonesian Health Survey reported an incidence of 24.8% among lactating mothers in North Sumatra Province. This study aimed to determine the effectiveness of cabbage leaf compresses in reducing breast engorgement among postpartum mothers at the Nining Pelawati Midwife Clinic, Lubuk Pakam District, in 2025. A quasi-experimental design with a one-group pretest–posttest approach was used. A total of 35 postpartum mothers experiencing breast engorgement were selected through total sampling. The intervention consisted of cold cabbage leaf compresses applied twice daily for 20–30 minutes. Data were analyzed using the Wilcoxon test to compare engorgement levels before and after the intervention. Before treatment, most respondents experienced moderate (65.7%), severe (22.9%), and mild (11.4%) engorgement. After the intervention, engorgement levels decreased to mild in 65.7% of respondents, moderate in 28.6%, and severe in only 5.7%. Statistical analysis showed a significant difference between pre- and post-intervention conditions (Z = -3.140; p = 0.002). In conclusion, cabbage leaf compresses are significantly effective in reducing breast engorgement in postpartum mothers. This non-pharmacological method is recommended as a safe, simple, and cost-effective alternative for managing postpartum breast swelling.